Income effect in inter-island passenger mode choice for the Western Visayas Region, Philippines - Roxas, Nicanor R. Jr (Philippine Engineering Journal)
This research aims to determine the presence of income effect in the inter-isalnd passenger transport of Panay and Negros in the Western Visayas region of the Philippines. This effect is of great significance for developing countries where the transportation expenditure may comprise a substantial fraction of the household budget. In this research, logit choice models for each income class combination were specified. Results showed that income effect exists in the dataset since the marginal utilities of income among income classes differ significantly. This result is important in mode choice modeling for the inter-island passenger transport in the region. Accounting for income effect leads to unbiased model parameter estimates. The models also indicate that mode choice is affected by total cost and ration of access time to total travel time.